Does reluctance to share personal data reduce citizen demand for personalized services? Evidence from a survey experiment - Florencia Aguirre; Benjamin Roseth; Julieth Santamaria (Inter-American Development Bank (IDB), 2024)
Two seemingly contradictory trends have accompanied the rise of digital transformation: a demand for better and more customized services, which require the use of personal data, and a concern for data protection. How do we reconcile these divergent trends? The answer to this question may influence not only the design of personalized services but also the strategies for their widespread adoption. This study explores how to mitigate the impact of citizens reluctance to share data on the uptake of personalized public services. Through a survey experiment, we offered two hypothetical personalized services: one educational service (a scholarship) and one health-related service (a checkup). Each respondent was randomly assigned to one of three possible intervention groups, receiving different types of information: (i) a summary outlining the service benefits; (ii) details on benefits with a data usage disclosure; and (iii) a data usage disclosure. The findings reveal that citizens exhibit a strong baseline interest in personalized services. However, a requirement to share personal data had an adverse impact on interest in both the educational and health-related services, resulting in declines of 2.6 to 3.0 percentage points. There are indications that the decrease in interest may be more pronounced for the health service. Providing detailed service descriptions increased interest by 4.5 and 5.5 percentage points for education and health services, respectively. This suggests that offering information about the benefits of the service can offset concerns about data privacy. These effects remained consistent among different population groups.
Keywords: D78; D90; H41; H83; 330; data protection; personal data; government services; citizen preferences